Evaluation of damage-based material models for carbon fiber-reinforced polymer composite laminate under mixed-mode bending - Masoud Pourasghar Lafmejani, 1987- author; Mohd. Nasir Tamin, supervisor; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2014